PENGARUH KONTROL DIRI TERHADAP EMOSI NEGATIF PADA SISWA KELAS XI IPA - Agus Heriyanto; Jayadi Jayadi; Zailatul Aufa (STKIP MUHAMMADIYAH SAMPIT, 2018)
The ability of self-control in every individual is very important because it can reduce or suppress negative emotions that arise unnoticed. An individual who can control his emotions will be able to make decisions wisely. This study is intended to know the influence of self control on negative emotion tested on grade XI science program students of SMAN 2 Sampit period 2015/ 2016. Hypothesis floated in this research was there is positive and significant influences between self control and negative emotion on grade XI science program students. This study is uses quantitative method expostfacto. There were 195 students from grade XI science program tested in this study and the samples taken were 25% from the whole and found 50 students as the respondent. Furthermore, the technique used on this phase was Proporsional Random Sampling. The result of the data analysis in this study uses the hypothesis test with t test shows that the score of ttest were -4,388 and the significances were 0,000 (p ≤ 0,05). Furthermore, the coefficient determination (R2) found were 0,286 which means, in this study, self control influenced to negative emotion as big as 0,286 or 28,6%. This result proved that self control significantly and possitively influences to negative emotion on grade XI science program students of SMAN 2 Sampit period 2015/ 2016, so the hypothesis floated in this research is accepted.